A Case Report of Premalignant Plasma Cell Dyscrasia-Induced Renal Failure in a 31-Year-Old Female - Ayrton Bangolo; Mahabuba Akhter; Amer Jarri; Manpreet Kaur; Ali Atoot; Parul Jandir; Mahmood Ibrahim; Lochana Manandhar; Adam Atoot (Case Reports in Hematology)
Monoclonal gammopathy of renal significance (MGRS) is a rare disorder in which monoclonal immunoglobulin secreted by nonmalignant B cell or plasma cell clone causes kidney damage. Although MGRS is a premalignant condition, it can cause severe kidney disease and end-stage renal disease (ESRD) at any age. Herein, we present a 31-year-old female with past medical history of lupus nephritis who presented with signs of volume overload and worsening renal function despite adequate immunosuppressive therapy. Renal biopsy revealed heavy and light chain deposition consistent with MGRS. This case report demonstrates the importance of including MGRS in the differential diagnosis of worsening renal function despite adequate treatment, raising awareness of this premalignant yet morbid condition.